Exploring the Quarter Life Crisis: Management Dimensions and Factors Influencing Early Adulthood Transitions Across Cultures and Educational Backgrounds - Dhita Fadhillah Azza; Muhammad Krisnanda Candra Mahkota; Gilar Bagus Permana; Lucia Rini Sugiarti; Fendy Suhariadi (Journal of Educational Management Research, 2025)
This study aims to identify the factors that influence the quarter-life crisis in early adulthood. A qualitative method was employed to reveal and understand this phenomenon within its unique context as experienced by individuals. Data were collected through observation and interviews and were analyzed using coding techniques. The findings indicate that anxiety about the future, pressure from family, fear of disappointing parents, and low self-confidence are key factors. Individuals also tend to compare themselves with others, particularly those deemed more successful. Various emotional responses, including frustration, hopelessness, and disappointment, were identified. The study also highlights the role of religious beliefs in coping with the crisis, although not all participants found this approach effective. Support from family and close friends is considered essential in overcoming the crisis, along with accepting one’s life process and engaging in self-exploration. Educational institutions can support early adults by offering mentorship, career guidance, and stress management programs, helping students navigate the quarter-life crisis and transition smoothly into adulthood while promoting emotional well-being and resilience.